Polyvinyl alcohol film, optical film comprising same, and preparation method thereof
By performing specific water immersion, drying and analytical steps in the manufacturing process of polyvinyl alcohol film, ensuring uniform distribution of its microstructure, solving the problems of uneven polarization and fringe defects in the polarization film, and achieving high polarization uniformity and stripe-free optical film.
Patent Information
- Application Number
- CN202311265935.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-31
- Filing Date
- 2023-09-28
- Publication Date
- 2025-02-14
AI Technical Summary
When the existing polyvinyl alcohol films are made into polarized films, they often lead to uneven polarization and fringe defects on the surface due to uneven microstructure distribution.
During the manufacturing process of polyvinyl alcohol film, differential scanning heat method (DSC) analysis was used after pure water immersion and drying, so that the total peak distance of the crystallization temperature was 0.1 to 3°C, and the expansion was controlled after immersion in water. The wetness was between 10% and 19% or more than 22%, and small angle X-ray scattering (SAXS) analysis was performed under 23°C/50% RH to ensure that the peak peak of the scattering intensity was less than 0.06 nm-1.
The microstructure distribution of the polyvinyl alcohol film is achieved, ensuring that the polarizing film produced has no stripe defects and uniform polarization, improving the optical properties.
Smart Images

Figure CN119431980A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyvinyl alcohol (PVA) film which can be used as an optical film, in particular a polarizing film. Background Art
[0002] Polyvinyl alcohol (PVA) film is a hydrophilic polymer with good transparency, mechanical strength, water solubility and processability. It has been widely used in packaging materials or optical films of electronic products, especially polarizing films.
[0003] The manufacturing methods of preparing optical films from polyvinyl alcohol resin can be divided into coating method and blow molding method. The coating method is to make the film-making stock solution into a finished product through the steps of defoaming, coating, drying, etc.; the blow molding method is to make the film-making stock solution into a finished product through the steps of defoaming, film blowing, biaxial stretching, drying, etc. Since the polyvinyl alcohol film made by the blow molding method often has scratches and stripes on the surface, while the polyvinyl alcohol film made by the coating method has better performance (such as smooth surface), the coating method is generally used to manufacture polyvinyl alcohol film at present.
[0004] When manufacturing polarizing film, uneven distribution of microstructure will cause lines on the surface of the polarizing film, which will in turn affect the uniformity of polarization. Therefore, the preparation process will reduce the surface lines as much as possible to obtain a polyvinyl alcohol film with better optical properties.
[0005] A good polarizing film has the characteristics of no stripe defects and uniform polarization, and can provide better optical properties. In order to improve the optical properties of polarizing films, the existing technology will improve the optical properties by improving equipment technology and selecting related component materials. Summary of the invention
[0006] However, when using the prior art polyvinyl alcohol film to prepare an optical film, the polarization degree is still often uneven. The inventors of this case found that it may be because the microstructure of the polyvinyl alcohol film in the original film that has not yet been made into a polarizing film is unevenly distributed, resulting in stripe defects on the surface of the final polarizing film and the phenomenon of uneven polarization.
[0007] Therefore, in order to solve the above problems, the present invention provides a polyvinyl alcohol film having a uniform microstructure distribution, so that the polyvinyl alcohol film can be made into a polarizing film without stripe defects and with uniform polarization degree.
[0008] One of the purposes of the present invention is to provide a polyvinyl alcohol film, in which, in differential scanning calorimetry (DSC) analysis after being immersed in pure water and dried, the peak range of the crystallization temperature is 0.1 to 3°C, and the peak difference of the heat flow relative temperature change curve after the first-order differential is 2 to 7°C.
[0009] In a preferred embodiment, the peak value of the crystallization temperature of the polyvinyl alcohol film is greater than or equal to 206°C.
[0010] In a preferred embodiment, after the polyvinyl alcohol film is immersed in water for 30 seconds, the swelling degree along the width direction (TD) is 10% to 19%.
[0011] In a preferred embodiment, after the polyvinyl alcohol film is immersed in water for 15 minutes, the swelling degree along the width direction (TD) is greater than 22%.
[0012] Another object of the present invention is to provide a polyvinyl alcohol film, wherein in a small angle X-ray scattering (SAXS) analysis after standing for 24 hours under the conditions of 23°C / 50%RH, the scattering vector (q) is 0.3 to 0.7 nm. -1 The total distance between the scattering intensity (I(q)) peaks is less than 0.06nm -1 .
[0013] In a preferred embodiment, the degree of polymerization of the polyvinyl alcohol film is between 1800 and 3000.
[0014] Another object of the present invention is to provide an optical film, which is made from the polyvinyl alcohol film of the present invention.
[0015] In a preferred embodiment, the optical film is a polarizing film.
[0016] In a preferred embodiment, the standard deviation of the polarization degree of the polarizing film measured at multiple positions is less than 0.006.
[0017] Another object of the present invention is to provide a method for manufacturing a polyvinyl alcohol film, comprising: (a) drying a polyvinyl alcohol resin and then washing it with water; (b) stirring and heating the polyvinyl alcohol resin, a surfactant, a plasticizer and water until they are dissolved to form a polyvinyl alcohol casting solution; (c) casting the polyvinyl alcohol casting solution onto a casting drum and drying it to obtain a primary formed film; and (d) contacting the primary formed film with a plurality of hot rollers whose temperatures decrease from high to low, and then entering a plurality of sections of an oven for heat treatment.
[0018] In a preferred embodiment, in step (a) of the method for manufacturing the polyvinyl alcohol film, the drying temperature of the polyvinyl alcohol-based resin is 115-125°C.
[0019] In a preferred embodiment, in step (a) of the method for manufacturing the polyvinyl alcohol film, the water-to-material ratio of the water washing is greater than or equal to 9.
[0020] In a preferred embodiment, in step (c) of the method for manufacturing the polyvinyl alcohol film, the wind speed difference along the width (TD) direction of the casting drum during drying is less than or equal to 2.5 m / s.
[0021] In a preferred embodiment, in step (d) of the method for manufacturing the polyvinyl alcohol film, the total contact time between the initially formed film and the hot roller having a temperature greater than 85° C. is 6 to 20 seconds.
[0022] In a preferred embodiment, in step (d) of the method for manufacturing the polyvinyl alcohol film, the temperature standard deviation of the oven along the width (TD) direction is less than 2.6.
[0023] The effect of the present invention lies in that the polyvinyl alcohol film provided by the present invention has a uniform microstructure distribution, and when it is subsequently used to make an optical film, it can have high polarization uniformity and no stripe defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a temperature drop curve diagram of a DSC analysis method of a polyvinyl alcohol film according to an embodiment of the present invention, differentiated using Origin data analysis software;
[0025] Figure 2 is a SAXS scattering diagram of a polyvinyl alcohol film according to an embodiment of the present invention;
[0026] Figure 3 Schematic diagram of the reaction between iodine ion dyeing and the amorphous region of polyvinyl alcohol when the polyvinyl alcohol film is dyed according to one embodiment of the present invention;
[0027] Figure 4 FIG. 1 is a schematic diagram of a test piece with an area of 10 cm*10 cm cut out of a polyvinyl alcohol film according to an embodiment of the present invention. DETAILED DESCRIPTION
[0028] The following embodiments should not be considered to unduly limit the present invention. Those skilled in the art may modify and alter the embodiments discussed herein without departing from the spirit or scope of the present invention, and still fall within the scope of the present invention.
[0029] The terms "a", "an" and "a" as used herein represent that there is one or more than one (ie, at least one) of the grammatical object herein.
[0030] The present invention provides a polyvinyl alcohol film, wherein in differential scanning calorimetry (DSC) analysis after being immersed in pure water and dried, the peak range of the crystallization temperature is 0.1-3°C, and the peak difference of the heat flow relative temperature change curve after the first order differential is 2-7°C.
[0031] The "crystallization temperature" described herein is the temperature required for a substance to transform from a liquid into a crystal, and the "peak value of the crystallization temperature" refers to the Tc,p (peak of crystallization temperature) value, which is the average value of the crystallization temperatures at a plurality of (for example, but not limited to 3) positions on the test sample. In a preferred embodiment, the peak value of the crystallization temperature is greater than or equal to 206°C, for example: greater than or equal to 206°C, greater than or equal to 206.5°C, greater than or equal to 207°C, and greater than or equal to 207.5°C.
[0032] The aforementioned "full range" refers to the difference between the maximum and minimum numbers in a set of data, which is the full range of this set of data, and the "peak full range of crystallization temperature in differential scanning calorimetry (DSC) analysis" is the Tc,p deviation, which refers to the value obtained by subtracting the minimum value from the maximum value after obtaining the crystallization temperatures at multiple (for example but not limited to 3) positions on the test sample in the differential scanning calorimetry (DSC) analysis. In a preferred embodiment, the peak range of the crystallization temperature of the polyvinyl alcohol film is 0.1-3°C, for example: 0.1-3°C, 0.1-2.5°C, 0.1-2°C, 0.1-1.5°C, 0.1-1°C, 0.1-0.5°C, 0.5-3.°C, 0.5-2.5°C, 0.5-2°C, 0.5-1.5°C, 0.5-1°C, 1-3°C, 1-2.5°C, 1-2°C, 1-1.5°C, 1.5-3°C, 1.5-2.5°C, 1.5-2°C, 2-3°C, 2-2.5°C, 2.5-3°C.
[0033] The aforementioned "peak difference of the heat flow relative temperature curve after first-order differentiation" refers to the heat flow relative temperature curve obtained by differential scanning calorimetry (DSC) analysis. The measurement schematic diagram is shown in FIG. Figure 1As shown, software (such as Origin data analysis software) is used to perform differentiation to obtain a differential line, the highest value near the crystallization peak is defined as Tc,2 and the lowest value is defined as Tc,1, Tc,1-Tc,2 is calculated, and the value obtained by taking the average of Tc,1-Tc,2 at multiple (for example but not limited to 3) positions. In a preferred embodiment, the peak difference of the heat flow relative temperature change curve of the polyvinyl alcohol film after the first order differential is 2-7°C, for example: 2-7°C, 2-6.5°C, 2-6°C, 2-5.5°C, 2-5°C, 2-4.5°C, 2-4°C, 2-3.5°C, 2-3°C, 2-2.5°C, 2.5-7°C, 2.5-6.5°C, 2.5-6°C, 2.5-5.5°C, 2.5-5°C, 2.5-4.5°C, 2.5-4°C, 2.5-3.5°C, 2.5-3.7 ℃, 3~6.5℃, 3~6℃, 3~5.5℃, 3~5℃, 3~4.5℃, 3~4℃, 3~3.5℃, 3.5~7℃, 3.5~6.5℃, 3.5~6℃, 3.5~5.5℃, 3.5~5℃, 3.5~4.5℃, 3.5~4℃, 4~7℃, 4~6.5℃, 4~6℃, 4~5.5℃, 4~5℃, 4~4.5℃, 5~7℃, 5~6.5℃, 5~6℃, 5~5.5℃, 6~7℃, 6~6.5℃, 6.5~7℃.
[0034] The present invention utilizes the peak full range of crystallization (Tc, p deviation) and the peak difference (Tc, 1-Tc, 2) after the first-order differential of the heat flow relative temperature change curve as indicators of crystallization temperature distribution. The larger the value, the greater the crystallization temperature deviation or the wider the distribution, which means that the microstructure distribution is more uneven, and the easier it is to cause the formation of surface lines of the polarizer after the polyvinyl alcohol film.
[0035] In a preferred embodiment of the present invention, the polyvinyl alcohol film of the present invention has a swelling degree of 10% to 19% along the width direction (TD) after being immersed in water for 30 seconds. In another preferred embodiment of the present invention, the polyvinyl alcohol film of the present invention has a swelling degree of more than 22% along the width direction (TD) after being immersed in water for 15 minutes.
[0036] The "swelling degree" mentioned in this article refers to the measurement of the length change of a polymer substance before and after it swells in a solvent, i.e. Cross-linked polymers cannot be dissolved in solvents. Solvents can only penetrate into the network structure of polymers to cause them to swell. The greater the network density of the polymer, the less likely the solvent will enter the network structure, and the smaller the swelling degree. Temperature and solvent will affect the swelling degree of polymers. The greater the interaction between the solvent and the polymer, the greater the swelling degree. "After immersion in water for 30 seconds" means placing a test piece with a fixed width (TD) direction length (for example, 10 cm) in a 30°C constant temperature water tank, and measuring the width (TD) direction length after immersion for 30 seconds. Without being limited to any theory, the inventors found that after the polyvinyl alcohol film was immersed in water for 30 seconds, the swelling degree along the width (TD) direction (hereinafter referred to as 30-second TD swelling degree) was too high or too low, which would cause lines on the surface of the final polarizer. In a preferred embodiment, the swelling degree of the polyvinyl alcohol film along the width (TD) direction after immersion in water for 30 seconds was 10% to 19%.
[0037] The term "immersed in water for 15 minutes" as used herein means placing a test piece of a fixed length in the width (TD) direction (e.g., 10 cm) in a 30°C constant temperature water tank, and measuring the swelled width (TD) length after immersion for 15 minutes. In a preferred embodiment, the degree of swelling of the polyvinyl alcohol film in the width (TD) direction (hereinafter referred to as 15-minute TD swelling) is greater than 22% after the polyvinyl alcohol film is immersed in water for 15 minutes.
[0038] The present invention further provides a polyvinyl alcohol film, wherein after being left to stand for 24 hours under the conditions of 23°C / 50%RH, in a small angle X-ray scattering (SAXS) analysis, a scattering vector (q) of 0.3 to 0.7 nm is obtained. -1 The total distance between the scattering intensity (I(q)) peaks is less than 0.06nm -1 .
[0039] The aforementioned "small angle X-ray scattering (SAXS)" is one of the methods for non-destructive research on the microstructure of materials. By using the scattering phenomenon of X-rays and electrons, SAXS can accurately observe and measure the microstructure of materials such as the size and size distribution, shape and directionality of nanoparticles and nanopores. The scattering vector (q) is defined as 4πλ -1 sinθ (with 2θ as the scattering angle), and conventional calibration with silver docosanoate; "scattering vector (q) is 0.3-0.7nm -1 The "scattering intensity (I(q)) peak full range" (hereinafter referred to as the scattering intensity peak full range)" refers to the SAXS analysis performed after standing for 24 hours under the conditions of 23°C / 50%RH (relative humidity), with the scattering intensity (I(q)) as the vertical axis and the scattering vector (q) as the horizontal axis. Figure 2 As shown, the scattering vector (q) is 0.3-0.7 nm. -1The position of the highest point of the scattering intensity (I(q)) corresponding to the data interval (because the scattering of the crystal plate structure of polyvinyl alcohol mostly falls within this interval) is obtained by subtracting the minimum value from the maximum value of the highest point data of multiple (for example but not limited to 3) samples of fixed area (for example, 1cm*1cm). In a preferred embodiment, this full distance is less than 0.06nm -1 , for example: less than 0.06nm -1 , less than 0.055nm -1 , less than 0.05nm -1 , less than 0.045nm -1 , less than 0.04nm -1 , less than 0.035nm -1 , less than 0.03nm -1 , less than 0.025nm -1 , less than 0.02nm -1 , less than 0.015nm -1 , less than 0.01nm -1 , less than 0.005nm -1 .
[0040] The aforementioned scattering vector (q) is 0.3 to 0.7 nm -1 The smaller the peak value range of the scattering intensity (I(q)) between the two regions is, the more uniform the microstructure distribution of the polyvinyl alcohol film is, so that the standard deviation of the polarization degree of the polarizer made from the polyvinyl alcohol film is smaller.
[0041] The "degree of polymerization" described herein is an indicator of the size of polymer molecules, which is the number of unit repeats in the polymer molecule. In a preferred embodiment, the degree of polymerization of the polyvinyl alcohol film is 1800 to 3000.
[0042] The "water content" mentioned in this article refers to the water content in a substance, which is defined as In a preferred embodiment, the water content of the polyvinyl alcohol film is 0.1 wt % to 5.0 wt %.
[0043] The present invention also provides an optical film, which comprises the polyvinyl alcohol film of the present invention.
[0044] The "optical film" described herein may refer to a polarizing film, an anti-blue light film, a filter film, etc., and the present invention is not limited thereto. Preferably, the polyvinyl alcohol film of the present invention is used as a polarizing film.
[0045] The "polarization degree" mentioned in this article refers to the ratio of the light intensity of the polarized part to the total light intensity, which is defined as Among them, H 0 H is the transmittance measured when two polarizing films are overlapped with each other in the same orientation direction;90 The transmittance is measured by overlapping two polarizing films with their orientation directions perpendicular to each other, wherein the measuring conditions of the present invention are, for example, subjecting the polyvinyl alcohol film to a polarizing film process (preparation process), using Perkin Elmer Lambda 365 as the measuring instrument, and measuring under the condition of 2 degree visible light sensitivity correction using C light source according to the standard method of JIS Z 8722 in 2009.
[0046] The "polarization degree measured at multiple positions" mentioned herein refers to multiple polarization degree data measured at multiple (for example, but not limited to 3) positions on a sample using the aforementioned polarization degree measurement method. In a preferred embodiment, the polarization degree of the polarizing film measured at multiple positions has a standard deviation of less than 0.006, for example: less than 0.006, less than 0.005, less than 0.004, less than 0.003, less than 0.002, less than 0.001.
[0047] The standard deviation is an indication of the dispersion of a set of data relative to the average value. A larger standard deviation means that the difference between most values and their average value is larger; a smaller standard deviation means that the difference between these values and their average value is smaller. The present invention uses the standard deviation of polarization to evaluate the uniformity of the polarization of the polarizing film. A larger standard deviation means that the polarization is more uneven; a smaller standard deviation means that the polarization is more uniform.
[0048] On the other hand, the present invention also provides a method for manufacturing the polyvinyl alcohol film, the steps of which include: drying a polyvinyl alcohol resin and then washing it with water; stirring and heating the polyvinyl alcohol resin, surfactant, plasticizer and water until they are dissolved to form a polyvinyl alcohol casting solution; casting the polyvinyl alcohol casting solution onto a casting drum and drying it to obtain a primary formed film; and contacting the primary formed film with a plurality of hot rollers whose temperatures decrease from high to low, and then entering a plurality of sections of an oven for heat treatment.
[0049] The above-mentioned polyvinyl alcohol resin is obtained by polymerizing vinyl ester resin monomers to form polyvinyl ester resins, and then performing saponification reaction; wherein the vinyl ester resin monomers include vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate or vinyl octanoate, and the present invention is not limited thereto, preferably vinyl acetate. In addition, copolymers formed by copolymerization of olefin compounds or acrylate derivatives with the above-mentioned vinyl ester resin monomers can also be used; the olefin compounds include ethylene, propylene or butene, and the present invention is not limited thereto. The acrylate derivatives include acrylic acid, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate or n-butyl acrylate, and the present invention is not limited thereto.
[0050] The maximum temperature of the polyvinyl alcohol resin is preferably controlled to be 115-125°C. According to at least one embodiment, the polyvinyl alcohol resin is dried at 115-125°C, for example, 115°C, 120°C or 125°C. If the temperature is higher than 125°C, local dehydration or cross-linking is likely to occur, making the crystallization temperature of the film uneven, Tc,1-Tc,2 larger, and Tc,p deviation larger; if the temperature is lower than 115°C, the resin is not dried enough, affecting productivity.
[0051] The dried polyvinyl alcohol resin is then washed with water to remove impurities (methanol, sodium acetate, etc.) in the resin, and the water-to-material ratio (weight ratio) is preferably greater than or equal to 9. According to at least one embodiment, the water-to-material ratio of the dried polyvinyl alcohol resin is greater than or equal to 9, for example, greater than 9 or greater than 10. If the water-to-material ratio is too low, impurities are not removed cleanly, and dehydration reaction is more likely to occur during film drying, causing Tc,1-Tc,2 to increase and Tc,p deviation to increase; if the water-to-material ratio is too large, the productivity of the polyvinyl alcohol film is affected.
[0052] The polyvinyl alcohol casting solution is prepared by stirring and heating the polyvinyl alcohol resin, surfactant, plasticizer and water until they are dissolved; the surfactant is, for example but not limited to, a cationic, anionic or nonionic surfactant, and the surfactant includes, for example but not limited to, carboxylate type such as potassium laurate; sulfate type such as sodium lauryl polyether sulfate; sulfonate type such as dodecylbenzene sulfonate; alkyl phenyl ether type such as polyoxyethylene octylphenyl ether; alcohol phenyl ether type such as polyethylene glycol monooctylphenyl ether; alkyl ester type such as polyoxyethylene laurate; alkyl amine type such as polyoxyethylene lauryl amino ether; alkyl amide type such as polyoxyethylene lauryl amide; polypropylene glycol ether type such as polyoxyethylene polyoxypropylene ether; alkanolamide type such as lauric acid diethanolamide and oleyl diethanolamide; allyl phenyl ether type such as polyoxyallyl phenyl ether, etc.
[0053] A polyvinyl alcohol casting solution is prepared, wherein a plasticizer can improve the processability of the film. The plasticizer that can be used is, for example, but not limited to: phthalate (Phthalate), 2-ethylhexyl phthalate (DEHP), glycerol, dibutyl phthalate (DBP), diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), butylbenzyl phthalate (BBP), dioctyl phthalate (DOP), ethylene glycol, propylene glycol, diethylene glycol, diglycerol, triethylene glycol, tetraethylene glycol or trimethylolpropane, etc.
[0054] The preparation of the primary formed film is to cast the polyvinyl alcohol casting solution onto a casting drum and then dry it. The casting solution is defoamed by a twin-screw extruder, extruded from a T-slit die lip, and cast onto a rotating high-temperature casting drum for drying and film formation; wherein the twin-screw extruder has good feeding performance, mixing and plasticizing performance, exhaust performance and extrusion stability performance, which can make the casting solution fully dispersed, stirred, compressed, and mixed to improve the production capacity of film manufacturing; the size of the extruded material is controlled to an appropriate thickness and good uniformity through the T-slit die lip. In addition, in a more preferred embodiment, the wind speed difference in the width (TD) direction of the air side of the casting drum is controlled to be less than or equal to 2.5m / s, preferably 1m / s, for example: 2.5m / s, 2.0m / s, 1.5m / s, 1.0m / s, wherein the "wind speed difference" refers to the full range of wind speed measured at multiple (for example but not limited to 3) positions in the width (TD) direction. The inventors found that if the wind speed difference in the width (TD) direction of the casting drum is larger, the long-period distribution of the final polyvinyl alcohol film will be more uneven, and the polarization degree will also be more uneven. The long period is obtained from the position of the peak in the SAXS data; in the process of forming a polarizer from the polyvinyl alcohol film, iodine ions will react with the amorphous region of the polyvinyl alcohol when dyeing, such as Figure 3 As shown, if the long period is not uniform along the width direction, it will cause the polarization degree to be non-uniform.
[0055] The preformed film is heat treated by contacting the preformed film with a plurality of hot rollers with decreasing temperatures from high to low, and then entering a drying oven with a plurality of sections for heat treatment. After the preformed film is peeled off from the casting drum, it is dried on both the upper and lower surfaces by contacting a plurality of hot rollers. The number of hot rollers is not particularly limited and can be adjusted as needed. According to at least one preferred embodiment, the total contact time of the initially formed film with the hot roller with a temperature greater than 85° C. is 6 to 20 seconds, preferably 10 seconds, for example: 6 to 20 seconds, 6 to 18 seconds, 6 to 16 seconds, 6 to 14 seconds, 6 to 12 seconds, 6 to 10 seconds, 6 to 8 seconds, 8 to 20 seconds, 8 to 18 seconds, 8 to 16 seconds, 8 to 14 seconds, 8 to 12 seconds, 8 to 10 seconds, 10 to 20 seconds, 10 to 18 seconds, 10 to 16 seconds, 10 to 14 seconds, 10 to 12 seconds, 12 to 20 seconds, 12 to 18 seconds, 12 to 16 seconds, 12 to 14 seconds, 14 to 20 seconds, 14 to 18 seconds, 14 to 16 seconds, 16 to 20 seconds, 16 to 18 seconds, 18 to 20 seconds. If the total contact time is too short, less than 6 seconds, the surface crystallinity of the PVA film is insufficient, which will cause excessive swelling in the width (TD) direction, and darker lines will appear when it is processed into a polarizer. After repeated research and experiments, it is concluded that if the total contact time of the hot roller is too long, greater than 20 seconds, the surface crystallinity of the polyvinyl alcohol film is too high, which will cause insufficient swelling in the width (TD) direction, and lines will appear when it is processed into a polarizer.
[0056] In addition, the formed film then enters a floating oven (FD) with a plurality of sections for heat treatment. The number of ovens is not particularly limited and can be adjusted as needed. According to at least one preferred embodiment, the temperature standard deviation of the oven along the width (TD) direction is less than 2.6, for example: less than 2.6, less than 2.4, less than 2.2, less than 2.0, less than 1.8, less than 1.6, less than 1.4, less than 1.2, less than 1.0, less than 0.8, less than 0.6, less than 0.4, less than 0.2. The inventors have found that if the temperature standard deviation of the oven along the width (TD) direction is greater than or equal to 2.6, the long period of the PVA film will be unevenly distributed along the width (TD) direction, resulting in uneven polarization when processed into a polarizer. Example
[0057] Hereinafter, the present invention will be further described with detailed description and examples. However, it should be understood that these examples are only used to help the present invention to be more easily understood and are not used to limit the scope of the present invention.
[0058] Provided below is a non-limiting method for preparing polyvinyl alcohol film. According to a method similar to the method disclosed below, 8 non-limiting examples of polyvinyl alcohol films (Examples 1-8) and 5 comparative examples of polyvinyl alcohol films (Comparative Examples 1-5) were prepared. However, the specific methods for preparing Examples 1-8 and Comparative Examples 1-5 will generally differ from the methods disclosed below in one or more aspects.
[0059] Specifically, the method for manufacturing the polyvinyl alcohol film comprises the following steps: drying polyvinyl alcohol resin particles at a temperature process shown in the table below to obtain a raw material. Before the polyvinyl alcohol raw material, plasticizer, water, etc. are uniformly dissolved, the raw material polyvinyl alcohol is first washed with water to remove impurities (sodium acetate, etc.), and then uniformly dissolved with the plasticizer, water, etc. to obtain a film-making stock solution. The molding stock solution is defoamed by a double-screw extruder, spit out from the T-row slit die lip, and cast onto a rotating high-temperature casting drum for drying and molding. By controlling the wind speed difference along the width (TD) direction of the air side of the casting drum, the primary mold is peeled off from the casting drum and then contacted with multiple hot rollers to dry the film to obtain the upper and lower surfaces, and the total contact time between the film and the hot roller is controlled. Then, a floating oven (FD) is used for heat treatment, and the temperature difference of the oven along the width (TD) direction is controlled to finally obtain a polyvinyl alcohol film product.
[0060] Examples 1-8 and Comparative Examples 1-5 were evaluated to determine the properties of the polyvinyl alcohol films. Tables 1 and 2 provide the processes of Examples 1-8 and Comparative Examples 1-5, a summary of the properties of the polyvinyl alcohol films, and the polarization uniformity of the polyvinyl alcohol films, respectively.
[0061] Table 1
[0062] Table 2
[0063] The casting drum air side wind speed difference (TD direction) in the above table is the full range of wind speed along the width (TD, Transverse Direction) direction, and is the value obtained by subtracting the minimum value from the maximum value of the wind speed at the three measured positions.
[0064] The peak value of crystallization temperature (Tc, p value) in the above table is obtained by DSC measurement method, which includes pre-treatment and crystallization temperature analysis. The pre-treatment is to divide the polyvinyl alcohol film into three equal parts in the width direction, and cut the middle of the divided polyvinyl alcohol film. The cutting area of each piece is (10 cm along the machine direction (MD) * 10 cm along the width direction (TD), such as Figure 3 As shown, a 10 cm*10 cm test piece is immersed in 2000 ml of 30°C pure water, stirred with a magnet for 5 minutes, and then taken out. The above steps are repeated once to ensure that the additives are washed out; the wet film is then placed in a 105°C oven for drying for 1 hour, and the film is taken out to obtain the test sample. Among them, the crystallization temperature analysis is to take 3 to 5 mg of the sample for DSC analysis. The method is to maintain the sample at 40°C for 1 minute, then increase the temperature to 250°C at a rate of 10°C / min, maintain it at 250°C for 1 minute, and then cool it down to 30°C at a rate of 10°C / min, and the crystallization temperature is recorded. The average of the crystallization temperatures at the three locations can obtain the Tc,p value.
[0065] The peak range of the crystallization temperature (Tc,p deviation) in the above table is obtained by analyzing the DSC measurement method, and the crystallization temperatures at three locations are obtained. The Tc,p deviation is obtained by subtracting the minimum value from the maximum value.
[0066] The peak difference (Tc,1-Tc,2 value) of the heat flow relative temperature change curve in the above table after the first-order differentiation is obtained by analyzing the DSC measurement method. The cooling curve is differentiated using the Origin data analysis software to obtain the differential line (such as Figure 1 As shown in the figure, the lowest value of the line near the crystallization peak is defined as Tc,1, and the highest value is defined as Tc,2. Tc,1-Tc,2 is calculated, and the average value of Tc,1-Tc,2 at the three positions is taken to obtain the Tc,1-Tc,2 value, which is used as an indicator of crystallization temperature distribution.
[0067] The specific methods of the 30-second TD swelling analysis in the above table include: sample preparation method and test method. The sample preparation method is to divide the polyvinyl alcohol film in the width (TD) direction into three equal parts, and cut the middle of the divided polyvinyl alcohol film. The cutting area of each piece is (MD 10 cm * TD 10 cm), and the test sample is obtained. The test method is to place the test sample in a 30°C constant temperature water tank, start the timing at the same time, measure the TD length after swelling after immersion for 30 seconds, and calculate
[0068] The 15-minute TD swelling degree analysis in the above table includes the following specific methods: sample preparation method and test method. The sample preparation method is to divide the polyvinyl alcohol film in the width (TD) direction into three equal parts, and cut the middle of the divided polyvinyl alcohol film. The cutting area of each piece is (MD 10 cm * TD 10 cm), and the test sample is obtained. The test method is to place the test sample in a 30°C constant temperature water bath, start the timing at the same time, measure the TD length after swelling after immersion for 15 minutes, and calculate
[0069] The SAXS peak position deviation in the above table is obtained by the SAXS analysis method, and its specific analysis methods include: sample preparation method and test method. Among them, the sample preparation method is to divide the polyvinyl alcohol film in the width direction into three equal parts, and cut the middle of the polyvinyl alcohol film into a test piece with an area of (1 cm * 1 cm). After the sample is left to stand for 24 hours under 23°C / 50% RH (relative humidity), SAXS analysis is performed. Among them, the test method is to use the BL23A small-angle X-ray scattering beamline of the Synchrotron Radiation Center in Taiwan for SAXS analysis at 0.3-0.7nm -1 The scattering vector (q) is defined as 4πλ. -1 sinθ (scattering angle in 2θ) was routinely calibrated with silver docosanoate, and all data were further corrected for sample transmission, background, and detector sensitivity.
[0070] The line evaluation method in the above table is to visually observe whether there are lines on the film surface during the polarizer manufacturing process.
[0071] The polarization degree in the above table can be obtained from the polarization degree determination method, and its specific analysis method includes sample preparation method and test method. Among them, the sample preparation method is to subject the polyvinyl alcohol film to the polarizer process. Among them, the test method is to use Perkin Elmer Lambda 365 as the test instrument, according to the standard method of JIS Z 8722 in 2009, use C light source to perform 2 degrees of visible light visual correction, and then overlap two polarized films with the same orientation direction, and measure the transmittance (H) at the wavelength. 0 ); Two polarizing films were overlapped with the orientation direction perpendicular to each other, and the transmittance (H 0 ), and calculate
[0072] The standard deviation of polarization in the above table is obtained from the polarization measurement method, and can be obtained by taking the standard deviation of the polarization at three positions.
[0073] According to the examples in Table 1, it can be found that when the polyvinyl alcohol film manufacturing process of the present invention is used to make a polarizing film, the surface of the polarizing film obtained is free of stripes and has excellent and uniform polarization degree.
[0074] Without being limited to a specific theory, the inventors have found that the maximum temperature of the polyvinyl alcohol resin dryer in the polyvinyl alcohol film process parameters mainly affects the Tc, p value and the Tc, 1-Tc, 2 value. As shown in the results of Comparative Examples 1-5, when the temperature is too high, the Tc, p value and the Tc, 1-Tc, 2 value will become larger, which is prone to local dehydration or cross-linking, making the film crystallization temperature uneven and causing the formation of lines on the surface of the polarizing film.
[0075] The water-to-material ratio in the polyvinyl alcohol film process parameters mainly affects the Tc, p value and the Tc,1-Tc,2 value. As shown in the results of Comparative Examples 4 and 5, when the water-to-material ratio is too small, dehydration reaction is more likely to occur, causing the Tc, p value and the Tc,1-Tc,2 value to increase, which is likely to cause lines on the surface of the polarizing film.
[0076] The total contact time with the hot roller greater than 85°C in the polyvinyl alcohol film process parameters mainly affects the 30-second TD swelling. As shown in the results of Comparative Examples 2-4, when the total contact time is too short, the surface crystallinity will be insufficient, the TD swelling will be too large, and the polarizer produced will have darker lines; when the total contact time is too long, the surface crystallinity will be too low, the TD swelling will be insufficient, and the polarizer produced will also have lines.
[0077] The standard deviation of the oven temperature (TD direction) and the wind speed difference on the air side of the casting drum (TD direction) in the process parameters of the polyvinyl alcohol film mainly affect the SAXS peak position deviation. As shown in the results of Comparative Examples 2 and 3, when the standard deviation of the oven temperature (TD direction) is too large and the wind speed difference on the air side of the casting drum (TD direction) is too large, it is easy to cause the long period of the polyvinyl alcohol film to be uneven in the TD direction, and the polarization degree of the obtained polarizer to be uneven.
[0078] Herein, all ranges provided are intended to include each specific range within a given range and combinations of sub-ranges between the given ranges. In addition, unless otherwise stated, all ranges provided herein include the endpoints of the ranges. Thus, ranges 1-5 specifically include 1, 2, 3, 4, and 5, as well as sub-ranges such as 2-5, 3-5, 2-3, 2-4, 1-4, etc.
[0079] All publications and patent applications cited in this specification are incorporated herein by reference, and each individual publication or patent application is specifically and individually indicated to be incorporated herein by reference for any and all purposes. In the event of any inconsistency between this document and any publication or patent application incorporated herein by reference, this document controls.
[0080] As used herein, the terms "including", "having" and "comprising" have an open, non-restrictive meaning. The terms "a", "an" and "the" are to be understood to encompass the plural as well as the singular. The term "one or more" means "at least one" and thus may include a single feature or a mixture / combination of features.
[0081] Except in the operating examples or where otherwise indicated, all numbers indicating amounts of ingredients and / or reaction conditions may in all cases be modified by the term "about", meaning within ±5% of the indicated number. As used herein, the terms "substantially free" or "substantially free" refer to less than about 2% of a particular feature. All elements or features that are positively set forth herein may be negatively excluded from the claims.
Claims
1. A polyvinyl alcohol film, wherein in a differential scanning calorimetry (DSC) analysis after being immersed in pure water and dried, the peak range of the crystallization temperature is 0.1 to 3°C, and the peak difference of the heat flow relative temperature change curve after the first order differential is 2 to 7°C. 2 . The polyvinyl alcohol film according to claim 1 , wherein the peak value of the crystallization temperature is greater than or equal to 206° C. 3 . The polyvinyl alcohol film according to claim 1 , wherein the degree of swelling of the polyvinyl alcohol film in the width direction (TD) is 10% to 19% after being immersed in water for 30 seconds. 4 . The polyvinyl alcohol film according to claim 1 , wherein after being immersed in water for 15 minutes, the degree of swelling along the width direction (TD) is greater than 22%.
5. A polyvinyl alcohol film, wherein after being left to stand for 24 hours under the conditions of 23°C / 50%RH, in a small angle X-ray scattering (SAXS) analysis, a scattering vector (q) of 0.3 to 0.7 nm is obtained. -1 The total distance between the scattering intensity (I(q)) peaks is less than 0.06nm -1 . 6 . The polyvinyl alcohol film according to claim 1 , wherein the degree of polymerization of the polyvinyl alcohol film is between 1800 and 3000. 7 . The polyvinyl alcohol film according to claim 1 , wherein the water content of the polyvinyl alcohol film is between 1.0 and 5.0 wt %.
8. An optical film made from the polyvinyl alcohol film according to any one of claims 1 to 7.
9. The optical film of claim 8, which is a polarizing film.
10. The optical film of claim 9, wherein the standard deviation of polarization degrees of the polarizing film measured at a plurality of positions is less than 0.
006.
11. A method for producing a polyvinyl alcohol film according to any one of claims 1 to 7, comprising: (a) drying a polyvinyl alcohol-based resin, and then washing with water; (b) stirring and heating the polyvinyl alcohol resin, surfactant, plasticizer and water until dissolved to form a polyvinyl alcohol casting solution; (c) casting the polyvinyl alcohol casting solution onto a casting drum and drying to obtain a preformed film; and (d) The preformed film is brought into contact with a plurality of hot rollers whose temperatures decrease from high to low, and then enters a plurality of ovens for heat treatment. 12 . The method for producing a polyvinyl alcohol film according to claim 11 , wherein in step (a), the drying temperature of the polyvinyl alcohol-based resin is 115 to 125° C.
13. The method for producing a polyvinyl alcohol film according to claim 11, wherein in step (a), the water-to-material ratio of the washing is greater than or equal to 9.
14. The method for producing a polyvinyl alcohol film according to claim 11, wherein in step (c), the wind speed difference along the width (TD) direction of the casting drum during drying is less than or equal to 2.5 m / s.
15. The method for producing a polyvinyl alcohol film according to claim 11, wherein in step (d), the total contact time between the initially formed film and the hot roller having a temperature greater than 85°C is 6 to 20 seconds.
16. The method for producing a polyvinyl alcohol film according to claim 11, wherein in step (d), the temperature standard deviation of the oven along the width (TD) direction is less than 2.6.